USE OF CONCRETE USING MOLTEN STEEL AS AGGREGATES: A LITERATURE REVIEW - Correa Zeña, Andy (2023)
The construction industry is composed of various materials whose components must play a fundamental role, such as the case of concrete, which depends mainly on the properties of cement and aggregates that make it up. However, today there is the incorporation of innovative products for its elaboration, such as molten steel. The purpose of this paper is to carry out a literature review on the effects of the use of molten steel as aggregate in concrete in order to see its mechanical properties and its behavior, being adequate to counteract the cracks that occur in this material. A review of 50 refereed and indexed articles was made. The keywords used were: use of concretes using molten steel as aggregates and molten steel fi bers. Finally, from the review, it is concluded that designs are usually obtained with biaxial behavior and multiaxial stresses instead of uniaxial stresses and high resistance capacity.  Keywords: cast steel – concrete – compressive – fl exural and compressive strength